2022
DOI: 10.3390/diagnostics12123224
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Device-Related Infections Due to Emerging Pathogens Diagnosed by a Combination of Microbiological Approaches: Case Series and Literature Review

Abstract: Orthopedic and trauma device-related infections (ODRI) due to high virulence microorganisms are a devastating complication after orthopedic surgery. Coagulase-negative Staphylococci (CoNS) are mainly involved but commensal bacteria, located in human mucous membranes, are emerging pathogens in ODRI. Currently, bacterial culture is the gold standard for ODRI but the diagnostic process remains time consuming and laborious. We evaluated a combination of microbiological approaches in the diagnosis of emerging patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Moreover, in half of the cases, an infection with multiple causative pathogens was noted. The data concur with those reported by Vasso et al [5], who determined the incidence and predictors of failure in patients treated with two-stage reimplantation for PJI and found that the number of highly virulent bacterial infections increased due to inappropriate antibiotic treatment strategies in community and health care settings [36][37][38]. Other studies have also reported that Pseudomonas aeruginosa infection and PJI caused by multiple causative bacteria were risk factors for amputation [39].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, in half of the cases, an infection with multiple causative pathogens was noted. The data concur with those reported by Vasso et al [5], who determined the incidence and predictors of failure in patients treated with two-stage reimplantation for PJI and found that the number of highly virulent bacterial infections increased due to inappropriate antibiotic treatment strategies in community and health care settings [36][37][38]. Other studies have also reported that Pseudomonas aeruginosa infection and PJI caused by multiple causative bacteria were risk factors for amputation [39].…”
Section: Discussionsupporting
confidence: 87%
“…The BD phoenix and VITEK 2 systems are based on automated biochemical reactions to enhance the efficacy of the microbial identification products [ 34 35 ]. Recently, this method was developed using a fluorescence system to detect the metabolic changes produced by various microorganisms [ 36 ]. An accuracy, positive predictive value (PPV), and negative predictive value (NPV)of 98%, 86%, and 99%, respectively, were achieved for the diagnosis of contagious and EM [ 32 ].…”
Section: Mastitis Diagnosismentioning
confidence: 99%
“…Veterinarians and farmers have been using (cow-side or on-site) tests to detect mastitis as they require relatively little training. Somatic cell counting detects milk quality and screens for intramammary infections [ 36 ]. The Se, Sp, and accuracy of SCC were 86.60%, 97.76%, and 91.94%, respectively, with a PPV and NPV of 98.33% and 84.52%, respectively [ 39 ].…”
Section: Mastitis Diagnosismentioning
confidence: 99%
“…In line with what has been said so far, PCR performed on feces could be the most promising tool for the diagnosis of H. pylori infection due to its numerous strengths: (i) high sensitivity and specificity, (ii) rapid execution, (iii) low costs, (iv) significant reduction in TAT compared to conventional methods (<1 day using PCR vs. >7 days through culture isolation), and (v) possibility of performing genotypic antibiogram directly from biological samples, overcoming the issue of bacterial growth. However, molecular techniques need confirmation through conventional methods, especially regarding fastidious pathogens, because (i) bacterial DNA positivity does not imply vitality, (ii) evaluation of resistance gene expression does not necessarily imply translation into proteins, and (iii) the genotypic antibiogram does not provide a MIC value [75][76][77]. However, the execution of PCR on biopsy samples remains controversial in light of the few studies in the literature.…”
Section: Molecular Diagnostic Approachmentioning
confidence: 99%